2022
DOI: 10.3847/2041-8213/ac5823
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Rates and Demographics of Tidal Disruption Events: Effects of the Disk Formation Efficiency

Abstract: Tidal disruption events (TDEs) are valuable probes of the demographics of supermassive black holes as well as the dynamics and population of stars in the centers of galaxies. In this Letter, we focus on studying how debris disk formation and circularization processes can impact the possibility of observing prompt flares in TDEs. First, we investigate how the efficiency of disk formation is determined by the key parameters, namely, the black hole mass M BH, the stellar mass m … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In this section, we compare our model predictions to the observed properties of TDEs. We start from the TDE catalog in Gezari (2021), which also lists the observed blackbody luminosities and temperatures, and then only include TDEs that have their masses estimated from the M-σ relation as in Wong et al (2022). This gives us 7 X-ray selected TDEs (Table D1) and 16 optically selected TDEs (Table D2).…”
Section: Comparison With Observations: Blackbody Luminositymentioning
confidence: 99%
“…In this section, we compare our model predictions to the observed properties of TDEs. We start from the TDE catalog in Gezari (2021), which also lists the observed blackbody luminosities and temperatures, and then only include TDEs that have their masses estimated from the M-σ relation as in Wong et al (2022). This gives us 7 X-ray selected TDEs (Table D1) and 16 optically selected TDEs (Table D2).…”
Section: Comparison With Observations: Blackbody Luminositymentioning
confidence: 99%
“…In this section, we compare our model predictions to the observed properties of TDEs. We start from the TDE catalog in Gezari (2021) which also lists the observed blackbody luminosities and temperatures, and then only include TDEs which have their masses estimated from the M − σ relation as in Wong et al (2022). This gives us 7 X-ray-selected TDEs (Table C.1) and 16 optically-selected TDEs (Table C.2).…”
Section: Comparison With Observations: Blackbody Luminosity Effective...mentioning
confidence: 99%
“…Moreover, Charlton et al (2019) have shown the total stellar mass of SDSS J0159 is about 4.7 × 10 10 M ⊙ , indicating the central BH mass about 6 × 10 6 M ⊙ (the accepted value in Wong et al (2022)) in SDSS J0159 through the correlation between central BH mass and total stellar mass as discussed in Haring & Rix (2004); Sani et al (2011); Kormendy & Ho (2013); Reines & Volonteri (2015), roughly consistent with the BH mass estimated by the M-sigma relation reported in our previous paper Zhang et al (2019). Therefore, besides the virial BH mass through virialization assumption to BLRs clouds and the BH mass through the M-sigma relation and through the total stellar mass, BH mass of SDSS J0159 determined through one another independent method will be very interesting and meaningful.…”
mentioning
confidence: 96%
“…Among the reported TDE candidates, SDSS J0159 is an interesting object, because its central virial BH mass reported as ∼ 10 8 M ⊙ in LaMassa et al (2015); Merloni et al (2015) through the virialization assumptions (Peterson et al 2004;Greene & Ho 2005;Vestergaard & Peterson 2006;Kelly & Bechtold 2007;Rafiee & Hall 2011;Shen et al 2011;Mejia-Restrepo et al 2022) applied to BLRs (broad emission line regions) clouds, the largest BH mass among the reported BH masses of TDE candidates in Wevers et al (2017); Mockler et al (2019); Zhou et al (2021); Wong et al (2022). However, variations of accretion flows have apparent effects on dynamical structures of BLRs, if the BLRs clouds are tightly related to TDEs, such as the more detailed abnormal variabilities of broad emission lines in the TDE candidate ASASSN-14li in Holoien et al (2016): strong emissions leading to wider line widths of broad H which are against the expected results by the Virialization assumptions to BLRs clouds.…”
mentioning
confidence: 99%